Proceso atención de enfermería en paciente con diagnóstico de fibrosis hepática, cirrosis y colangitis biliar. - Rea Manobanda, María Teresa (2024)
The nursing care process is essential for providing appropriate care to patients facing various pathologies. Hepatic cirrhosis is characterized by the progressive destruction of liver parenchyma and alterations in liver structure. It is a silent disease that progresses slowly, with symptoms typically appearing in advanced stages. In the development of this clinical case, a 48-year-old patient with a diagnosis of hepatic cirrhosis was considered, taking into account the needs according to Gordon's functional patterns and the taxonomic requirements of NANDA, NOC, and NIC. This allowed for the provision of appropriate and beneficial care through the implementation of the Nursing Care Process (NCP). Conditions such as hepatic fibrosis and cirrhosis represent progressive stages of liver deterioration, increasing vulnerability to infections like biliary cholangitis. The latter is a complication resulting from acute inflammation and infection of the bile ducts, frequently caused by gallstones. A detailed understanding of these pathologies is essential for nursing staff, allowing the application of specific and effective care that improves the patient's condition, providing care that prioritizes quality and empathy, thus ensuring the patient's well-being and rapid recovery.